2018
DOI: 10.1177/0143831x18804655
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity, employability and satisfaction among temporary and permanent employees in post-crisis Europe

Abstract: Earlier studies established that perceived job insecurity is more strongly related to the experiences of permanent employees, and conversely that perceived employability is more strongly related to the experiences of temporary employees. We challenge these results against the background of the 2008/2009 crisis using samples from the 2010 European Social Survey with employees from Continental and Mediterranean Europe. First, we argue that job insecurity has become a structural phenomenon that associates with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 64 publications
4
46
0
Order By: Relevance
“…This suggests that permanent employees may have more at stake in their work and therefore job insecurity may especially threaten vitality in this group. This finding aligns with some previous studies which have also shown that permanent employees may suffer more from job insecurity than temporary workers [56][57][58]. The explanation for this may lie in the psychological contract theory, which differentiates between relational psychological contract and transactional contract [58].…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…This suggests that permanent employees may have more at stake in their work and therefore job insecurity may especially threaten vitality in this group. This finding aligns with some previous studies which have also shown that permanent employees may suffer more from job insecurity than temporary workers [56][57][58]. The explanation for this may lie in the psychological contract theory, which differentiates between relational psychological contract and transactional contract [58].…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…Further, experiences of job insecurity depend on three threat features: perceived situational control, threat duration and volition. Consequently [23], lower control, longer duration and lower volition will cause increased distress in workers, with detrimental effects on personal physical and psychological health and work-related well-being [5,[23][24]. Finally, other authors [26] have proposed differentiating the cognitive components of job insecurity related to the perception of loss or negative job change, from the affective components related to the emotional reactions to job loss or potential job change.…”
Section: Consequences Of Job Insecurity On Mental Health and Health Cmentioning
confidence: 99%
“…Although job insecurity and perceived employability are comparable in that they are subjective perceptions regarding the future (De Witte et al, 2015), there is an important distinction: job insecurity relates to the future of the current job, whereas perceived employability concerns future jobs – be these with the current employer or another (De Cuyper et al, 2018). De Witte and De Cuyper (2015) summarized the relationship between job insecurity and perceived employability from two points of view.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned job demands-resources model, in which job insecurity as job demand can affect extrinsic and intrinsic dissatisfaction, while perceived employability as personal resource can affect higher intrinsic and extrinsic levels of satisfaction (Lu et al, 2015; De Cuyper et al, 2018), has led to the following hypothesis:…”
Section: Introductionmentioning
confidence: 99%